ANALISIS TINDAK TUTUR DALAM BUKU BACAAN “LEGENDA CERITA RAKYAT NUSANTARA” - Asti Nur Pratiwi; Aninditya Sri Nugraheni (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2020)
This mini research aims to: (1) describe speech acts contained in the writing of the book "Legenda Cerita Rakyat Nusantara", (2) explain the meaning of speech acts contained in the reading book. This mini research uses descriptive qualitative research type. To analyze the data through several stages, namely the stage of reading, identifying, categorizing, describing, and concluding. Data sourced from the book reading "Legenda Cerita Rakyat Nusantara" by Cahaya Fadilah published by Pustaka Anak Bangsa. The results obtained from this mini research are as follows: (1) the speech acts contained in the reading book "Legenda Cerita Rakyat Nusantara" are localized acts of speech, illocution and perlocution, (2) the speech acts contained in the reading book are meaningful for ask / pray, declare, decide, rule, and invite. Keywords: speech acts, readings books